Altruistic works, religion, and corruption: Kiais’ leadership to shape anti-corruption values in pesantren - Abdul Karim; Oman Fathurrohman; Muhammadun; Wahyu Saripudin; Diding Rahmat; Firman Mansir (Cogent Social Sciences)
This study investigates the several roles of kiais (leaders) in pesantren, such as the Kiais’ behaviors in instilling anti-corruption teachings, Kiais’ words containing anti-corruption messages, and Kiais’ policies in supporting anti-corruption programs in IBS. This research was a qualitative method that examined Kiai“s leadership to shape anti-corruption values in pesantren with a phenomenological approach. The research participants were 12 Kiais as subjects in Bendakerep pesantren. Data collection methods included interviews, observation by delivering questionnaires to 15 students, and documentation by using descriptive analysis. The results indicated that Kiais” behavior in inculcating anti-corruption teaching builds change and confidence in their students, motivates them, and helps to ensure social trust. Kiais’ words and policy relate to anti-corruption values and mentality at the individual, family, and societal levels. Where the discussion is that all Kiais inspire their followers and prohibit acts of corruption, but only the Bendakerep Kiai is an anti-corruption figure who sets an example with altruistic works, namely not involved in politics, even Islamic mass organizations and refusing outside funding but remains obedient to government provisions under Islamic law. This research outcome contributes to the best practice and current knowledge of altruistic works leadership, religion, and anti-corruption behaviors in pesantren.